2004
DOI: 10.1007/s00063-004-1004-y
|View full text |Cite
|
Sign up to set email alerts
|

Versorgungsqualität im medikamentösen und präventiven Bereich bei Patienten mit und ohne koronare Herzkrankheit

Abstract: Drug therapy, primary and secondary prevention in the observed subjects were fairly poor. Remarkable deficits in health care quality became obvious. There is no lack in availability of evaluated, effective and efficient measures. Thus, physicians' efforts to implement evidence-based guidelines into clinical practice have to be strengthened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For example, the German follow-up of the Hypertension Evaluation Project clearly demonstrated inadequate knowledge of the diagnosis and treatment of arterial hypertension 30. Further, there is evidence that deficiencies in treatment quality appear to be the result of inadequate implementation of existing cardiologic treatment recommendations (among other factors) 21,31. On the other hand, the results of a recent survey indicated that there is essentially no difference in the treatment provided by physicians knowledgeable in the guidelines and those who were less familiar 11…”
Section: Discussionmentioning
confidence: 99%
“…For example, the German follow-up of the Hypertension Evaluation Project clearly demonstrated inadequate knowledge of the diagnosis and treatment of arterial hypertension 30. Further, there is evidence that deficiencies in treatment quality appear to be the result of inadequate implementation of existing cardiologic treatment recommendations (among other factors) 21,31. On the other hand, the results of a recent survey indicated that there is essentially no difference in the treatment provided by physicians knowledgeable in the guidelines and those who were less familiar 11…”
Section: Discussionmentioning
confidence: 99%
“…A German analysis evaluated that 47% of men and 59% of women received prescriptions for at least three of the four recommended drugs (antiplatelet drugs, β-blockers, ACE inhibitors, lipid-lowering agents) during the time between the initial myocardial infarction and a secondary event [10]. Another German study revealed that 83.6% of patients with a CHD history received antiplatelet drugs and 70.9% used β-blockers one year after the index event [11]. …”
Section: Introductionmentioning
confidence: 99%